Cuminum cyminum and Carum carvi: An update - Johri, R. K. (Pharmacognosy Reviews)
Cuminum cyminum and Carum carvi are the sources of cumin and caraway seeds respectively, which have been used since antiquity for the treatment of various indications in traditional healing systems in wide geographical areas. Cumin and caraway seeds are rich sources of essential oils and have been actively researched for their chemical composition and biological activities. In recent times (especially during the last 3 years) considerable progress has been made regarding validation of their acclaimed medicinal attributes by extensive experimental studies. In this attempt many novel bioactivities have been revealed. This review highlights the significance of cumin and caraway as potential source of diverse natural products and their medicinal applications.
Keywords: Caraway; Carum carvi; cumin; Cuminum cyminum chemistry; pharmacology